Wielding power in multiparty negotiations: the impact of communication medium and assertiveness. Issue 1 (2nd October 2021) - Lee, Jonathan I.; Jang, Daisung; Luckman, Elizabeth A.; Bottom, William P.
Abstract : Purpose: The medium negotiators choose for communication will influence both process and outcome. To understand how medium influences power expression, this paper aims to compare value claiming by asymmetrically powerful negotiators, using face-to-face and computer-mediated messaging across two studies. Following up on long-standing conjectures from prominent coalition researchers, the authors also directly tested the role of the apex negotiator's personality in coalition formation and value expropriation. Design/methodology/approach: The authors conducted two laboratory experiments which manipulated communication medium (computer-mediated vs face-to-face) in three- and four-person bargaining. They also varied asymmetry of power so the apex negotiator either could not be left out of a winning coalition (Study 1) or could be (Study 2). The authors measured trait assertiveness along with multiple indicators of hard bargaining behavior. Findings: Communicating using instant messages via a computer interface facilitated value claiming for powerful negotiators across both studies. Trait assertiveness correlated with hard bargaining behavior in both studies. An index of hard bargaining behavior mediated the effect of assertiveness on value expropriation but only in the context where the powerful negotiator held a genuine monopoly over coalitions. Originality/value: The authors contribute to the literature on multiparty negotiations by demonstrating persistent media effects on power utilization and by finally confirming the conjectures of prominent coalition researchers regarding personality. Though personality traits generate consistent effects on behavior, their influence on negotiation outcomes depends on the power structure. Negotiation theory needs to incorporate structural and situational factors in modelling effects of enduring traits. Negotiation research should move beyond a rigid focus on dyads.